Acute hospital dementia care: results from a national audit - Timmons, Suzanne (BMC Geriatr, 2016)
BACKGROUND: Admission to an acute hospital can be distressing and disorientating for a person with dementia, and is associated with decline in cognitive and functional ability. The objective of this audit was to assess the quality of dementia care in acute hospitals in the Republic of Ireland. METHODS: Across all 35 acute public hospitals, data was collected on care from admission through discharge using a retrospective chart review (n = 660), hospital organisation interview with senior management (n = 35), and ward level organisation interview with ward managers (n = 76). Inclusion criteria included a diagnosis of dementia, and a length of stay greater than 5 days. RESULTS: Most patients received physical assessments, including mobility (89 %), continence (84 %) and pressure sore risk (87 %); however assessment of pain (75 %), and particularly functioning (36 %) was poor. Assessment for cognition (43 %) and delirium (30 %) was inadequate. Most wards have access at least 5 days per week to Liaison Psychiatry (93 %), Geriatric Medicine (84 %), Occupational Therapy (79 %), Speech & Language (81 %), Physiotherapy (99 %), and Palliative Care (89 %) Access to Psychology (9 %), Social Work (53 %), and Continence services (34 %) is limited. Dementia awareness training is provided on induction in only 2 hospitals, and almost half of hospitals did not offer dementia training to doctors (45 %) or nurses (48 %) in the previous 12 months. Staff cover could not be provided on 62 % of wards for attending dementia training. Most wards (84 %) had no dementia champion to guide best practice in care. Discharge planning was not initiated within 24 h of admission in 72 % of cases, less than 40 % had a single plan for discharge recorded, and 33 % of carers received no needs assessment prior to discharge. Length of stay was significantly greater for new discharges to residential care (p < .001). CONCLUSION: Dementia care relating to assessment, access to certain specialist services, staffing levels, training and support, and discharge planning is sub-optimal, which may increase the risk of adverse patient outcomes and the cost of acute care. Areas of good practice are also highlighted.